Attraction to Men and Women Predicts Sexual Dimorphism Preferences. Issue 1 (2nd January 2020) - Batres, Carlota; Jones, Benedict C.; Perrett, David I.
Abstract: Objectives: Sexual orientation categories are commonly differentiated in the partner preference literature. Yet little is known about how the variability within each category influences partner preferences. Methods: We investigated women's ( N = 27, 611) preferences for sexual dimorphism in male faces in relation to self-reports of sexual attraction to men/women (from 'not at all' to 'very'). Results: Self-identified heterosexual women reported considerable variation in sexual attraction levels. We found that sexual dimorphism preferences related positively with attraction to men and negatively with attraction to women. Conclusions: Such variability in women's sexuality should be taken into account when investigating partner preferences.